New Species of the Heterodermia comosa-Group (Physciaceae, Lichenized Ascomycota) from Southern South America - Michlig, Silvia Andrea (2017)
A revision of the specimens from southern South America deposited at CTES herbarium identified as Heterodermia comosa (Eschw.) Follmann & Redón was made. As a result, four new species, viz. H. mobergiana Michlig, M.P. Rodríguez & Aptroot, H. neocomosa M.P. Rodríguez L.I. Ferraro & Aptroot, H. ramosociliata M.P. Rodríguez, Michlig & Aptroot, and H. sorediosa Michlig, L.I. Ferraro & Aptroot, all closely related to H. comosa, are here proposed. Each species is described, illustrated and commented. A distribution map is also presented.